Effect of environmental integrity on the functional composition of the Odonata (Insecta) community in streams in the Eastern Amazon - Rocha, Tainã Silva; Calvão, Lenize Batista; Juen, Leandro; Oliveira-Junior, José Max Barbosa (Frontiers in Ecology and Evolution, 2023)
Anthropic activities affect the dynamics of aquatic communities and can influence the reproductive behavior of many species. In addition, functional diversity is expected to be influenced by the environment. In this context, we evaluated how the biological functional characteristics of the Odonata adult community respond to impacts caused by human action on streams in the eastern Amazon, using bionomic characteristics as response variables. Concomitantly, we analyzed which characteristics are responsible for the presence of species in the environment. We sampled adults of Odonata in 98 preserved and altered streams in the eastern Amazon. We used as functional characteristics: oviposition, thermoregulation and body size, and as morphological characteristics: width of the thorax, width of the wing at the base, length of the abdomen and length of the thorax. We recorded 80 species, distributed in 16 functional groups and three categories: present in all environments, present only in preserved environments, and present only in altered environments. There was variation in the functional characteristics studied between the environments (PerMANOVA; F = 15,655; P < 0.01), with a significant difference in the composition of attributes between the environments studied. Although PCoA did not find a strong relationship between the functional attributes and the level of integrity, the individuals found in altered areas are heliothermic, exophytic oviposition, with a wider wing width at the base and larger size. Individuals with smaller body size and endophytic and epiphytic oviposition, and thermal and endothermic conformators are found in preserved areas. Our study provides evidence that functional attributes are determining factors for the occurrence of species in the environment. The high quality of environment has a significant effect on the composition of functional groups. Exophytic and heliothermic species are favored by altered environments, while in preserved environments, the species that are best adapted are those that present epiphytic and endophytic oviposition and ectothermic thermoregulation (thermal conformers). As for morphology, altered environments favor medium to large individuals, with greater thorax length and abdomen size, preserved environments may favor the smaller and/or specialized species.